PERPETRATORS OF WORLD WAR І IN THE INTERPRETATION OF EMPEROR WILHELM II HOHENZOLLERN: VERIFICATION OF THE HISTORICAL VERSION - NADTOKA, Oleksandr (EAST EUROPEAN HISTORICAL BULLETIN, 2025)
The purpose of the article is to verify the historical version of the German Emperor Wilhelm II Hohenzollern regarding the perpetrators of the outbreak of the World War І. The research methodology is based on the principle of basic expansion of the interpretive field of the issue under research, verification, content analysis, comparative historical and comparative lexical methods, quantitative method when using thematic statistical research. The scientific novelty of the study consists in the return to scientific circulation of the historical version of Wilhelm II Hohenzollern regarding the culprits of World War І and the verification of this concept based on the study of the memoirs of the last German emperor, memories and works of politicians and diplomats from Germany, England, France, as well as analytical works of the Russian General headquarters, contemporary press, published diplomatic documents and statistical data. Conclusion. In his memoirs, the former German Emperor Wilhelm II Hohenzollern presented “historical tables” that were supposed to prove the falsity of the accusations of Germany and Austria-Hungary in the outbreak of World War І. The key thesis is that the war for Germany, under the conditions of the united and overwhelming forces of the Entente, looked like a losing strategy. The analysis of indicators of military capabilities presented in the article confirms this thesis of Wilhelm Hohenzollern and proves the impossibility of conducting a successful long-term war against the overwhelming forces of the enemy in a situation of strategic encirclement by enemy countries from the West, East and North (the advantage of the British Navy). France and Russia appear in the memoir as the behind-the-scenes power and the executive power. Great Britain, unlike France, did not directly contribute to the growth of Russiaʼs military power. The personal sources we have examined, such as the memoirs of French and British politicians and diplomats, as well as the fact that Russia was the first major European country to start military mobilization and create a real threat of war against Austria-Hungary and Germany, encourage us to take a closer look at the German version of events. In the end, Germany chose the established practice of declaring war on countries that threatened it in order to legitimately start mobilizing in response to Russian mobilization efforts. It is significant that British politicians recognized the peace-loving, or at least non-aggressive, mood in Berlin on the eve of the war. Key words: World War І, perpetrators, German Empire, Austro-Hungarian Empire, Russia, France, England, memoirs, historical tables, statistical data.